Old and new poems - Hall, Donald (New York : Clarion Books, 1984)
While little Lucy is out for a swim, various bunnies from the staff crowd into her family's hotel room.
Keywords: Children's stories, American; Hotels, motels, etc. -- Fiction; Rabbits -- Fiction